Alternative Management of a Pediatric Case of Hemorrhagic Cystitis due to BK Virus: Use of Thulium Laser Coagulation - Aydogan, Tahsin Batuhan (Eur Urol Open Sci, 2021)
We report on a pediatric case of hemorrhagic cystitis due to BK virus in a patient with acute lymphoblastic leukemia who had undergone bone marrow transplantation. A very large hematoma that almost completely filled the bladder was aspirated using a morcellator via suprapubic percutaneous access, and a thulium laser was then used to cauterize extensive areas of diffuse uroepithelial bleeding. This combined minimally invasive procedure was successful in clearing the bladder hematoma and achieving hemostasis.